FAHP-based assessment of courier service preferences among Malaysian users / Mohd Fazril Izhar Mohd Idris, Khairu Azlan Abd Aziz and Nurfilzah Muhammad Munib - Mohd Idris, Mohd Fazril Izhar; Abd Aziz, Khairu Azlan; Muhammad Munib, Nurfilzah (UiTM Cawangan Perlis, 2024)
This study addresses the problem of understanding users' preferences for courier services in Malaysia. As online shopping and package delivery become increasingly prevalent, it is essential to identify the key factors that influence users' decisions when choosing a courier service. The Fuzzy Analytical Hierarchy Process (FAHP) method is employed to tackle this problem. The study aims to determine the relative importance of criteria such as responsiveness, reliability, empathy, assurance, and tangibility, along with their corresponding sub-criteria. A group of experts defined these criteria and sub-criteria, and a questionnaire was distributed to gather data on customer preferences. Using the FAHP technique, the study constructed a hierarchy tree, created a fuzzy pairwise comparison matrix, and calculated criterion and sub-criteria weights. The findings highlight the importance of responsiveness, particularly easy contact with courier companies, as the primary criterion. Enhancing services based on these insights can help users select suitable courier services while improving competitiveness in the industry.